2017
DOI: 10.1097/mpa.0000000000000896
|View full text |Cite
|
Sign up to set email alerts
|

Local and Systemic Expression of Immunomodulatory Factors in Chronic Pancreatitis

Abstract: Inflammatory and fibrotic events that drive chronic pancreatitis (CP) are likely orchestrated via signaling of soluble cytokines and chemokines systemically and within the pancreas. However, a comprehensive summary of the expression of such factors during CP has not been reported to date. This information is important given continued interest in targeting cytokines that influence CP pathogenesis. Reported data on the expression change of soluble immunomodulatory factors in human CP patients were identified via… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
19
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(21 citation statements)
references
References 73 publications
(40 reference statements)
0
19
0
2
Order By: Relevance
“…Several pro-inflammatory mediators are associated with reduced quality of life in general or with worse specific function and symptom scores of the QLQ-C30 and PAN 28 questionnaires. While some of the inflammatory mediators were described in recent clinical and pre-clinical studies dealing with this issue, changed serum levels of most of the identified inflammatory mediators have not been associated to CP yet 12,18 . Patients with CP suffer from a diminished quality of life in general.…”
Section: Discussionmentioning
confidence: 96%
“…Several pro-inflammatory mediators are associated with reduced quality of life in general or with worse specific function and symptom scores of the QLQ-C30 and PAN 28 questionnaires. While some of the inflammatory mediators were described in recent clinical and pre-clinical studies dealing with this issue, changed serum levels of most of the identified inflammatory mediators have not been associated to CP yet 12,18 . Patients with CP suffer from a diminished quality of life in general.…”
Section: Discussionmentioning
confidence: 96%
“…It is known that inflammation and fibrosis in chronic pancreatitis are likely orchestrated via signalling of soluble cytokines and chemokines 39. We found that the expression of chemokines including Mcp1 , Ccl5 , Cx3cl1 and Icam1 was significantly increased in isolated Nrdc-cKO acinar cells at 3 weeks of age, when immune cell infiltration was not yet observed and that the expression of Cxcl10 was markedly increased in Nrdc- deleted acinar cells in ex vivo culture experiments.…”
Section: Discussionmentioning
confidence: 70%
“…The activation and resorption of the bone matrix, and the formation of new bones are processes that occur during the bone remodeling process ( 31 ). Chemokines are small proteins weighing 8–10 kDa, which serve important roles in host defense systems and help to maintain normal tissues status ( 32 , 33 ).…”
Section: Discussionmentioning
confidence: 99%